2019
DOI: 10.1186/s13071-019-3847-3
|View full text |Cite|
|
Sign up to set email alerts
|

Show us your ticks: a survey of ticks infesting dogs and cats across the USA

Abstract: BackgroundA variety of tick species infest dogs and cats in North America. Although most of these species also readily feed on people, national data regarding the species and abundance of ticks on dogs and cats are lacking. Here we report a large-scale study of ticks from dogs and cats in the USA over a 12-month period.MethodsTick submissions were invited from veterinary practices in all 50 states. Ticks were submitted with information about the pet and the attachment sites of each tick marked on a biopsy char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 36 publications
6
68
0
2
Order By: Relevance
“…Despite the widespread availability of preventives, ticks are common on dogs across the USA, and evidence suggests the prevalence of heartworm infection and of antibodies to tick-borne disease agents is increasing in some regions [ 9 12 ]. These increases likely result from a combination of factors including increased vector populations, resulting in more intense transmission, geographic spread of natural maintenance cycles for infection, and translocation of infected dogs [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread availability of preventives, ticks are common on dogs across the USA, and evidence suggests the prevalence of heartworm infection and of antibodies to tick-borne disease agents is increasing in some regions [ 9 12 ]. These increases likely result from a combination of factors including increased vector populations, resulting in more intense transmission, geographic spread of natural maintenance cycles for infection, and translocation of infected dogs [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 The black-legged tick, Ixodes scapularis , however, is the most commonly reported species of this genus in cats and dogs across eastern and southern USA. 11 Disease occurs by a salivary neurotoxin that is released into the host from the engorged female tick from the Ixodes genus. 2 In Australia, the I holocyclus tick causes a unique, more severe version of tick paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of this article [ 1 ], the authors found an error in Table 4 : the identity of the ticks from one cat, 32 larvae, had been incorrectly recorded as Dermacentor variabilis , while it is actually Ixodes cookei , as confirmed by re-examination of the original datasheet and tick specimens.…”
Section: Correction To: Parasites Vectors (2019) 12:595 101186/s1307mentioning
confidence: 99%